Republic of Lithuania : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
This 2006 Article IV Consultation highlights that following exceptional economic progress, based on macroeconomic stability and economic flexibility, imbalances and cautionary signals have emerged for Lithuania. Centered around nontraded goods production, GDP grew 7.5 percent in 2005. Most indicators suggest a tightening of resource use: a declining unemployment rate, high capacity utilization, and buoyant asset prices. The current account deficit has remained sizable, with significant reliance on bank and market-based financing to cover it. Rapid credit growth has supported a growing household appetite for mortgages and corporate demands in nontraded sectors.